SYNERGISING EXPERTISE: USM MEDIA HOUSE AND SOFTWARE HOUSE IN THE PIPELINE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 3 October 2015 – Universiti Sains Malaysia (USM) plans to synergise its various talents to establish USM’s Media House and Software House which will contribute not only towards fortification of its knowledge repository but also to impart an inclusive impact on the community.